Current detection methods of African swine fever virus - Hu, Zhiqiang; Tian, Xiaogang; Lai, Ranran; Wang, Xinglong; Li, Xiaowen (Frontiers in Veterinary Science, 2023)
African swine fever (ASF), caused by the African swine fever virus (ASFV), is a highly contagious and notifiable animal disease in domestic pigs and wild boars, as designated by the World Organisation for Animal Health (WOAH). The effective diagnosis of ASF holds great importance in promptly controlling its spread due to its increasing prevalence and the continuous emergence of variant strains. This paper offers a comprehensive review of the most common and up-to-date methods established for various genes/proteins associated with ASFV. The discussed methods primarily focus on the detection of viral genomes or particles, as well as the detection of ASFV associated antibodies. It is anticipated that this paper will serve as a reference for choosing appropriate diagnostic methods in diverse application scenarios, while also provide direction for the development of innovative technologies in the future.